Estimation of stature from forearm length in Thai children - Montip Tiensuwan, Kannika Song-in, Suda Riengrojpitak (Journal of Food Health and Bioenvironmental Science, 2015)
Abstract In cases where only incomplete human remains of an unknown person are recovered from the crime scene, the estimation of stature from these remains is particularly important in personal identification. The estimated stature may be used to narrow down the search in missing person databases. The present study aims to set appropriate regression equations to estimate stature from percutaneous forearm length for Thai school-age children (45 males and 45 females) ages between 5 and 19 years in the central region of Thailand. All subjects were healthy and had no physical deformities. Stature and forearm length were measured by using a stadiometer and a digital caliper. All measurements were recorded to the nearest millimeter. The data was analyzed using SPSS version 18.0 for Windows. Descriptive statistics, paired samples t-test, Pearson’s correlation analysis, linear Regressions, and multiple regression analysis were used. The results in the present study showed that the correlation coefficients between stature and forearm (ulna and radius) length are high and significant in both sexes (r = 0.988 - 0.992, p < 0.01). In Thai school-age children, forearm lengths (radial length) are highly correlated with stature (standard error of estimation range from ±2.7464 cm to ±3.1190 cm). The Multiple regression equations provide slightly better results than the linear regression equations. Therefore, the equations derived in the present study will be useful for stature estimation from forearm length in Thai children. Keywords: Estimation of stature, Forearm length, Thai children, Regression equation